Efektivitas Komunikasi Perawat terhadap Serah Terima Pasien - Olimpia de Jesus Araujo; Mira Triharini; Ilya Krisnana (Journal of Telenursing (JOTING), 2022)
This study aims to analyze the nurse's effective communication effect on patient handover. The method used is a systematic review by tracing articles on ScienceDirect, Ebsco and ProQuest using the terminology "handover" OR "handoff" AND "communication" OR "communicate" OR "communicating". The results showed that an effective strategy in the handover process was to use a collaborative approach between academics and physicians to improve patient safety and satisfaction, optimize resource use and ensure positive changes in practice. In conclusion, nurse's effective communication on patient handover improves patient safety and quality of patient care. Keywords: Nursing, Communication, Handover